Några internationella perspektiv på en forskningspolitik i förändring - Fredriksson, Martin (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2008)
We asked give former guest scholars to send us a short report on the current situation for cultural research in their home countries. This article is an attempt to summarise these reports and it touches on questions of funding, evaluating and conducting cultural and interdisciplinary research in Australia, New Zeeland, the United Kingdom, Finland and Israel. All reports tell of a situation where it is hard for cultural research to compete for funding with the social and natural sciences since the methods used for evaluating research quality tends to favour the latter. The current trend to allocate funding to research that is regarded as socially and economically useful is yet another disadvantage for cultural research whose outcomes might be hard to measure. Interdisciplinary research is affected by those general conditions, but it is also subject to specific conditions that vary in different countries. In some countries, such as Finland, interdisciplinary applications are met by a certain lack of understanding in a system of funding that is structured around a traditional order of academic disciplines. In other countries, such as New Zeeland, research funds look favourably upon interdisciplinary research. The main problem for Cultural studies seems to be that it has no natural place in the disciplinary landscape and that it is dispersed among many different departments. The main conclusion that can be drawn is however that both the disciplinary landscape and the systems for funding and evaluating research are currently under reconstruction in many parts of the world, but that the outcome of this process is still unpredictable.